Bernardita Reyes Churchill (Executive Editor), Eden M. Gripaldo, and Digna B. Apilado (Associate Editors). (2011). The movement for independence in the Philippines, 1896-1898: Calendar of documents in the archives of the Cuerpo de Vigilancia de Manila. Q - Planta, Ma. Mercedes G. (Social Science Diliman: A Philippine Journal of Society and Change; Vol 7 No 2 (2011), 2012)
none